INTEGRASI TANGGAPAN BACAAN INTERAKTIF UNTUK MENGAKSELERASI MINAT BACA SISWA SMP NEGERI 1KEDUNGWUNI - Keysa Salsabilla, Shafina; Yulieta Putri, Selvy; Syafaatillah, Sabila; Wahyu Widodo, Daffa; Ula Kusuma, Afaf; Rissa Shofiani (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2026)
An interest in reading is a crucial competency for students facing the demands of 21st-century learning, which emphasizes critical thinking, communication, collaboration, and creativity. While various literacy programs have been implemented in junior high schools, their execution often focuses on individual reading and responses, leaving limited room for the interaction and exchange of ideas among students regarding what they have read. This study aims to describe the implementation of integrating interactive reading responses as a strategy to boost student interest in reading at SMP Negeri 1 Kedungwuni and to identify the factors supporting this implementation. A qualitative method with a descriptive approach was employed. Data were collected through semi-structured interviews with Indonesian language teachers, library staff, and students, and subsequently analyzed through data sorting, presentation, and conclusion drawing; data validity was ensured through source triangulation. The results indicate that the interactive reading response process involves preparation, the reading activity itself, and subsequent student discussions and presentations regarding the reading material. Through these activities, students gain knowledge from their classmates' readings, practice articulating arguments and ideas critically, and become more motivated due to the freedom to choose reading materials that align with their interests. The teacher's role in guiding and motivating students, alongside the library's role in providing access to reading materials, contributes to the success of these activities. This study demonstrates that integrating interactive reading responses holds potential as a relevant alternative strategy for fostering student interest in reading at the junior high school level.